Métodos fotoeletroquímicos para determinação de antioxidantes - LIMA, Fernanda Maria dos Reis (2019)
The present work is based on the development of analytical methods for the determination of two antioxidants, propyl gallate (GP) and tannic acid (AT), respectively. In order to do this, two photoelectrochemical sensors were developed: the first one consisted of quantum dots of cadmium telluride (CdTe) and a polyelectrolyte, chitosan, using indium and tin oxide (ITO) as the electrode surface. This sensor was used for PG detection/quantification. The second sensor was composed of titanium dioxide (TiO2) - N-methylphenazone (PMS) methylsulfate co-sensitized with CdTe quantum dots and fixed with a film of nafion (Nf) on a surface of fluorine-doped tin oxide (FTO). This was applied for the detection/quantification of TA. The sensors developed were named ITO/CdTe-PDG and FTO/TiO2-PMS/CdTe/Nf. In both photoelectrochemical systems a commercial LED lamp was used as the source of irradiation. The characterization of the materials was performed by Electrochemical Impedance Spectroscopy (EIS) or Scanning Electron Microscopy (SEM) and Amperometry. The two developed sensors presented excellent electrochemical responses to the analytes of interest when compared to the responses obtained with the individual materials. The ITO/CdTe-PDG sensor showed great sensitivity to the dissolved oxygen in the electrolyte solution containing the analyte (PG), being proved the importance of this molecule in the buffer solution used. After optimization of the experimental and operational conditions, it was possible to obtain a linear range of response for the PG from 0.3 to 150 μmol L-1 for the ITO/CdTe-PDG sensor and from 0.2 to 200 μmol L-1 for the sensor FTO/TiO2-PMS/CdTe/Nf, with detection limits of 0.13 and 0.06 μmol L-1, respectively. The ITO/CdTe-PDG sensor was applied in samples of babassu oil and soybean oil for PG quantification, showing recovery values of 96.2 and 100.4%, respectively. The FTO/TiO2-MSF/CdTe/Nf sensor was applied in samples of medicinal plants extracts for TA quantification, with recovery values between 101.1 and 103.9%. The standard addition method was applied for quantification of the analytes in both types of samples. The two sensors showed good selectivity against the interfering species commonly found in these samples, besides good precision and accuracy.